Factors influencing patients' opt-in intention of exchanging health information - Zhang, Xijing; Zhang, Runtong (Frontiers in Public Health, 2022)
Introduction: Health information exchange (HIE) exhibits tremendous benefits in improving the quality of healthcare and reducing healthcare costs. However, it also poses challenges related to data security, data privacy, patient engagement, etc. Objective: This study aimed to explore the factors affecting patients’ opt-in intention to HIE by using an empirical study based on the theory of planned behavior. Methods: A Web-based survey was conducted involving 501 valid participants in China (69% validity rate). Results: Information sensitivity and perceived HIE transparency affected the patients’ opt-in intention to HIE through the mediation of perceived behavior control and trust in HIE. Information sensitivity negatively influenced perceived behavior control (-0.551, P<0.001) and trust in HIE (-0.489, P<0.001). Perceived transparency of HIE positively influenced perceived behavior control (0.396, P<0.001) and trust in HIE (0.471, P<0.001). Moreover, patients’ opt-in intention to HIE can be positively affected by perceived HIE transparency (0.195, P<0.001) and trust in HIE (0.294, P<0.001). In addition, the moderating effect of health status was positive and significant between trust in HIE and opt-in intention to HIE but not between the perceived behavior control and opt-in intention to HIE. Conclusions: This study contribute to the theory of planned behavior and enrich the literature on HIE efforts. HIE administrators should design personalized health services on the basis of these different health statuses to successfully achieve the patients’ opt-in intention to HIE.